Pengaruh Senam Aerobik Terhadap Peningkatan Kualitas Hidup Pada Penderita Diabetes Melitus Tipe II - Lupiansyah, Muhammad Ramli, Isnaini Herawati, SSt. FT, M. Sc (2016)
Background: Indonesian People who affected by Type II DM raised more toward following years. This finding needs seriously care because it will produce bad quality of life . Change life style is one of best treatment for this problem while they get Pharmacology treatment. One of it's method is Physical Exercise which had been suggested for several decade to avoid quality of life decrease. The correct aerobic exercise prescription for type II DM is low level aerobic exercise Objective: Knowing effect of aerobic exercise to gain quality of life for people with type II DM Research Method: This Research was quasi experiment with pre and post test design. 15 respondent was conducted which inclusion criteria was respondent should have blood glucose for> 200mg/dl. World Health Organization of Life (WHOOQOL)-BREF was used as quality of life parameter. Statistic analysis used Wilcoxon test. Result:Based on analysis data (p=0.008)>0.05. These result meant this research has effect for gaining quality of life for Type II DM . Conclusion: There is effectof aerobic exercise to gain quality of life for people with type II DM Key Words: Aerobic Exercise, Quality of Life, Type II Diabetes Mellitus.